Formyl peptide receptors at the interface of inflammation, angiogenesis and tumor growth. (December 2015) - Prevete, Nella; Liotti, Federica; Marone, Gianni; Melillo, Rosa Marina; de Paulis, Amato
Graphical abstract: Abstract: N -formyl peptide receptors (FPRs) belong to the family of pattern recognition receptors (PRRs) that regulate innate immune responses. Three FPRs have been identified in humans: FPR1–FPR3. FPR expression was initially described in immune cells and subsequently in non-hematopoietic cells and certain tissues. Besides their involvement in inflammatory disorders, FPRs have been implicated in the regulation of tissue repair and angiogenesis. Angiogenesis is not only a key component of pathogen defence during acute infection and of chronic inflammatory disorders, but also plays a critical role in wound healing and tissue regeneration. Moreover, pathologic uncontrolled angiogenesis is central for tumour growth, progression, and the formation of metastases. In this review, we summarise the evidence for a central role of FPRs at the intersection between inflammation, physiologic angiogenesis and pathologic neovascularisation linked to cancer. These findings provide insights into the potential clinical relevance of new treatment regimens involving FPR modulation.